The Influence of Varying Ar/O2Gas Ratio with Catalyst-Free Growth by Homemade Thermal Evaporation Technique - Azira Khairudin; Najiha Hamid; Syahida Suhaimi; Mohd Ikmar Nizam Mohamad Isa; Nur Athirah Mohd Taib; Syamsul Kamar Muhamad @ Wahab (Semarak Ilmu Publishing, 2024)
A nanostructured zinc oxide (ZnO) with different percentages of argon and oxygen gas flow rate was deposited on a silicon wafer by a simple hot tube thermal evaporation technique. The effect of different percentages of gas flow rate on the crystal structure, surface morphology and optical properties were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) and RAMAN spectroscopy, respectively. The changes of morphologies from FESEM were significant where the grown ZnO nanostructures show three different shapes which are nanotripods, nanoclusters and nanorods at 5%, 10% and 25% of oxygen gas, respectively. EDX results revealed that Zn and O elements have a major percentage in the sample indicating a composition has high purity of ZnO. XRD patterns displayed the most intense diffraction peak of ZnO at (101), which exhibited a single crystalline hexagonal structure with preferred growth orientation in the c-axis. RAMAN scattering study found that synthesized ZnO shows the high intensity of E2 mode and low intensity of E1 mode attributed to all the samples having good crystal quality containing fewer structural defects. In conclusion, the E15 sample with a 25% oxygen gas flow rate was selected as an optimum result for synthesizing a homogenous surface and high crystallinity of ZnO by using a hot tube thermal evaporation process. This work can enhance the development of ZnO production in various applications.